Pathogenesis and the most frequent symptoms of neurofibromatosis type 1 - Czajkowski, Grzegorz; Kałużny, Jakub; Jatczak-Gaca, Agnieszka; Wysocki, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
This study was to evaluate pathogenesis, symptoms, clinical course and possible treatment of neurofibromatosis type 1. Neurofibromatosis type 1, von Recklinghausen’s disease, is one of the phacomatoses. It belongs to the most frequent inherited diseases in human population. This disease is autosomal dominant, but new spontaneous mutation are also common. The symptoms are caused by disorders in the melanocytes and gliocytes. In ophthalmological examination Lisch nodules, caféau lait spots, neurofibromas of the lids, optic pathway gliomas and deformation of the orbit bones, can be observed. The symptoms are different, depend upon the age and demonstrate charateristic evolution through the lifetime.